Importance of vitamin D supplementation in pregnancy-review - Dkhar, Sabira Aalia; Ashraf, Ambrine; Hassan, Muzamil (International Journal Of Community Medicine And Public Health, 2019)
Pregnancy is a state that leads to several deficiency and increased demand of essential nutrients for the growing foetus. In one such case it is seen that vitamin D deficiency can lead to severe outcome in the new-born as well as the mother. Vitamin D travels to the foetus by passive transfer and the foetus is entirely dependent on maternal stores. Therefore it becomes all the more essential to know your vitamin D level during antenatal period to prevent adverse outcomes. Vitamin D supplementation helps in preventing the outcomes like rickets, low birth weight, bone and dental deformity in foetus, decreased immunity and impaired lung function in children, whereas also helping in decreased incidence of primary caesarean sections, preeclampsia, gestational diabetes mellitus in mother. The recommended dose has been described up to 2000IU/day as a supplementation and not therapeutic dose, which is found to be safe and effective.